The first, the next, and the cinematographed versions of AZT - JÍMENEZ, Paula C. (Vitae, 2014)
“Ronald Woodroof died of AIDS in September 12, 1992, seven years after he was diagnosed. A lower dose of AZT became widely used in later drug combinations that saved millions of lives”. These words end the film Dallas Buyers Club, a recent, highly awarded movie, that tells the true story of a cowboy diagnosed with AIDS in 1985 and illegally receives the firsthand antiviral AZT but, due to the severe side effects that the drug afflicted, begins to experiment with – and illicitly distribute among the “Club” – non-FDA approved remedies in search of a better treatment for himself and other AIDS patients. Perhaps owing to an artistic strategy, the movie waits until the last couple of lines to do justice to AZT and the impact it had in dealing with AIDS at that day and age.